GREEN ECONOMY MOVEMENT THROUGH THE UTILIZATION OF HOUSEHOLD COOKING OIL WASTE into VALUE-ADDED BUSINESS PRODUCTS - Chudri, Intan Rizkia; Purnamasari, Desy; Anggraini, Yessi (Universitas Muhammadiyah Aceh, 2025)
The reuse of cooking oil can be harmful for human health. Disposing of used cooking oil waste directly into the ground can also pollute the environment. These practices can endanger both human health and the environment. Cooking oil is one of the daily necessities for the Indonesian people. Therefore, raising public awareness about the dangers of reusing cooking oil must be continuously carried out. The facts show that many people still reuse cooking oil many times. This is often due to a lack of knowledge about its negative health impacts as well as financial constraints. Unfortunately, the increasing consumption of cooking oil and production of used cooking oil waste is not accompanied by greater public awareness of food and environmental health. From a medical perspective, consuming food processed with used cooking oil can pose serious health risks, as it contains substances that may cause degenerative diseases such as cancer, stroke, and other dangerous illnesses. Ideally, cooking oil should only be used a maximum of two times. Public awareness of environmental protection also remains low; waste used cooking oil is often improperly disposed of, leading to environmental contamination.Key words: Green Economy, Reuse cooking oil, household, Valuable Bisnis Product